Edukasi Pencegahan Penyakit Tidak Menular Melalui Gerakan Remaja CERDIK - Sari, Puspita; Ridwan, M.; Nasution, Helmi Suryani; Reskiaddin, La Ode; Kasyani, Kasyani (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2024)
Non-communicable diseases are the highest cause of death in Indonesia at 64%. The increase in deaths occurred due to high non-communicable diseases. The prevalence of non-communicable diseases has increased such as cancer reaching 1.8%, stroke 10.9%, chronic kidney disease at 3.8%, diabetes mellitus 8.5%, and hypertension 34.1%. This activity aims to provide health education about healthy lifestyles that must be applied from an early age in order to avoid non-communicable diseases with preventive and promotive steps. The activity was carried out by providing material on the prevention of non-communicable diseases through the CERDIK youth movement in Danau Embat Village, Batang Hari Regency in August 2024 with 35 adolescent subjects. Activities are carried out with the pre-test stage, the education and discussion implementation stage and the evaluation stage with the post-test. PkM activities with the acquisition of pre-test scores with a mean value of comparison between pre-test post-test is 1.70. There were also 27 (77%) respondents who increased their knowledge, 4 (11.5%) respondents who remained knowledgeable and 4 (11.5%) respondents who decreased their knowledge. The results of the bivariate analysis test with Wilcoxon T-Test on Pre-test and Post-test respondents showed a p value = 0.001 <0.05, so it can be concluded statistically that there is a significant difference in knowledge between knowledge before and after education.